(untitled) (Revista horizonte, 2022)
The aim of this study was to determine the correlation between the deep squat jump (DSJ) and the maximum repetition in the back squat (MR), to introduce DSJ as a tool for strength testing, training monitoring and control of strength in Crossfit®. The sample was of 9 male athletes (age 31.5±4.64 y/o; high 171,4±3,283 cm; body mass 79,29±7.14 kg; BMI 26,96±2.03 kg/m2) who performed both tests (DSJ and MR back squat test). A linear regression analysis wasperformed to determine the correlation and, subsequently, the relationship between DSJ and RM. The correlation of DSJ and RM squat was calculated using the Spearman R equation r=0,4167 showed a moderate relationship. The results showed a non-significant relationship with values for a p=0,2696